Model predictive current control for two-phase switches clamping of three-phase inverter. (December 2020) - Guo, Xifeng; Sun, Shaobin; Liang, Xue; Ning, Yi; Zheng, Di
Abstract: Traditional finite-control-set model predictive control has been widely concerned for heavy power voltage source inverters owing to its simplicity, as well as control flexibility. However, the drawbacks of widespread current harmonic, high switching loss and heavy computational burden are fully exposed. In this article, three-phase voltage source inverter is taken as the research object and a model predictive current control algorithm for two-phase switches clamping is proposed. Firstly, deadbeat control and delay compensation strategy are combined to calculate reference voltage vector and determine two legs that have maximum and minimum reference voltage vectors. Then, the optimal voltage vector set can be directly selected by clamping switches on two legs that have maximum and minimum reference voltage vectors, which decreases the number of commutations on three legs with a large current. The proposed algorithm not only reduces the switching loss and computational burden, but also increases the efficiency of operation. The simulation experiments are implemented to estimate the control effect of the proposed algorithm. Comparison results indicate the proposed algorithm can be more effective than existing algorithms.